EU’s political will versus EU’s political (in)action towards its Southern border: Promotion and protection of women’s rights in Morocco and Tunisia - Canário, M. (Europe as a Global Actor 2019, 2019)
In the 1970s, the United Nations together with the Netherlands, Sweden and Norway developed and applied the concept of Gender Mainstreaming, a strategy to promote gender equality through the inclusion of a gender perspective from the preparation process to the evaluation of public policies, regulations and budgets in order to end gender discrimination and promote gender equality using positive actions. The European Union used the Gender Mainstreaming concept for the first time in 1991. Since then, it has been applied not only internally but also regarding its foreign policy. Nonetheless, there is a gender-based discrimination problem inside the 28 Member states territory: in 2016, the gender pay gap was over 16% and, according to the European Institute for Gender Equality (EIGE), less than 1% of EU’s Structural and Investment Funds have been set aside for the promotion of gender equality. Also, the EU has been accused of imposing its ideals, norms and principles through the European Neighbourhood Policy (ENP), not having in consideration the culture, history, economical context, religion and social characteristics of its partners. This research seeks to contribute to understand the discrepancy between EU’s political will and EU’s political action concerning women’s rights in its Southern border, namely in Morocco and Tunisia.